Green Claims and Message Frames: How Green New Products Change Brand Attitude - Olsen, Mitchell C.; Slotegraaf, Rebecca J.; Chandukala, Sandeep R. (Journal of Marketing, 2014)
In response to a top ten global consumer trend, firms are increasingly introducing environmentally sustainable (“green”) new products. Firms allocate significant resources to this area; thus, the authors consider the brand-level implications by investigating how the introduction of green new products changes attitude toward the brand. In examining this relationship, they draw from social identity and framing theories to investigate drivers of green new product introductions as well as the moderating effects of message framing, source credibility, and product type. Estimating a three-stage least squares model based on new product introductions from 75 brands across a four-year time period (2009–2012), the authors find that green new product introductions can indeed improve brand attitude and that both the brand and category's positioning influence the introduction of green new products. They also find that the quantity of green messages, the product type, and their source credibility influence the extent to which green new products change brand attitude. The authors use these findings to provide guidance for managers as they attempt to effectively link their green innovation efforts to improve consumer attitudes toward their brands.